2007
DOI: 10.1007/s00264-007-0481-z
|View full text |Cite
|
Sign up to set email alerts
|

Computed-tomography-guided percutaneous radiofrequency thermoablation for the treatment of osteoid osteoma—2 to 5 years follow-up

Abstract: The purpose of this study is to evaluate the efficacy of the computed tomography (CT)-guided percutaneous radiofrequency thermoablation (PRT) method with a minimum of 2 years follow-up. Twenty-eight patients who were followed for more than 2 years among 35 patients who underwent CT-guided PRT between April 1999 and May 2005 were included in this study. The mean age was 24.5 years (range 7-55 years) and the mean follow-up period was 40.1 months (range 24-66 months). With a radiofrequency electrode, the lesion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 19 publications
5
34
2
Order By: Relevance
“…Through the years, several image-guided, minimally invasive interventions have been developed to treat OOs. CT-guided radiofrequency ablation (RFA) for OO [31], is one of the increasing numbers of minimally invasive alternatives to conventional operative procedures [10,31,38,42]. In one study limited to OOs in the upper extremity, the authors [37] reported complete resolution of pain without additional treatment in 76% of patients, equal to the minimum rate reported in a series not limited to any specific locations [8].…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…Through the years, several image-guided, minimally invasive interventions have been developed to treat OOs. CT-guided radiofrequency ablation (RFA) for OO [31], is one of the increasing numbers of minimally invasive alternatives to conventional operative procedures [10,31,38,42]. In one study limited to OOs in the upper extremity, the authors [37] reported complete resolution of pain without additional treatment in 76% of patients, equal to the minimum rate reported in a series not limited to any specific locations [8].…”
Section: Introductionmentioning
confidence: 74%
“…Several studies report the use of RFA for ablation of OO in usual and unusual locations [16,23,35,38]. In one study limited to OOs in the upper extremity, the authors reported complete resolution of pain without additional treatment in 76% of patients [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the use of computed tomography (CT)-guided percutaneous radiofrequency thermoablation (PRT) has been reported with good results and this has been shown to have similar recurrence rates to open surgery but with fewer complications and shorter periods of hospital stay [7,8]. Several studies have been published describing the outcome and side effects of RFA.…”
Section: Introductionmentioning
confidence: 99%